In Vitro Toxicity Evaluation of Caffeine Imprinted Polymer (CAF-MIP) for Decaffeination Method on Normal Chang Liver Cells - Hashim, Fatimah; Mehamod, Faizatul Shimal; Nawi, Naizatul Akmal (Makara Journal of Technology, 2017)
Over consuming of caffeine is one of the factors to a few health problems such as insomnia, hypertension and cardiovascular disease. This preliminary study was conducted to evaluate the Caffeine-Imprinted Polymer (CAF-MIP) toxicity that was synthesized for a new alternative method for decaffeination. It is crucial to evaluate the toxicity of CAF-MIPas this product is potential to be used as complimentary with any drinks containing caffeine. In this study, the CAF-MIP toxicity potential was confirmed on Normal Chang Liver cell (NCLC) based on its IC50 value andacridine orange and propidium iodide (AO/PI) staining for mode of cell death observation.Proliferation assay was also conducted after 24, 48 and 72 hours at 30 μg/ml on NCLC and it showed that CAF-MIP promote NCLC growth as shown by at various concentrationof CAF-MIPincrease the percentage of NCLC viability. Observation under light microscopes on NCLC incubated wit CAF-MIP and NIP showed the normal, viable cell morphology, cuboidal and monolayer cell morphology and this can be seen with green fluorescence when view under fluorescence microscope. In conclusion, from this study, it is proved that the CAF-MIP does not initiate toxicity effects on human liver cells, meanwhile induction of cell proliferation was observed.